(untitled) (BIRDEM Medical Journal, 2020)
Background: Pancreatitis is a serious disorder of pancreas. This study was designed to investigate the clinical features and outcomes of the hospitalized patients with acute pancreatitis (AP) with or without diabetic mellitus (DM). Methods: A total of 90 adult hospitalized patients with AP diagnosed in three different tertiary hospitals were evaluated for inclusion in prospective study on clinical, laboratory and outcome parameters. After exclusion according to exclusion criteria, 68 patients were enrolled finally, and out of 68 patients 34 were diabetic with AP from BIRDEM and 34 AP patients were non-diabetic from Dhaka Medical College and BSMMU. Results: The major clinical features, laboratory markers were significantly (p<0.05) higher whereas serum albumin levels was significantly (p<0.05) lower in diabetic AP group as compared to the non-diabetic AP group. DM was associated with severe form of AP compared to the non-diabetic group (p<0.05). Conclusions: The results of the present study suggest that DM increases the disease severity of AP. Therefore, clinicians should pay more attention in the treatment and management of acute pancreatitis if the patients have DM. Birdem Med J 2020; 10(3): 172-181